(untitled) - Johnson, David E. (Englewood Cliffs, N.J., 1986)
Contents: The first nine chapters of the book are devoted to terminology and time domain analysis and the last nine chapters deal with frequency-domain analysis.Also those on fourier methods and laplace transforms are often reserved for a succeeding course in linear systems, but their essential ingredients are here if there is time to cover them
Keywords: Phân tích mạch điện,Electric circuit analysis